Influências do compartilhamento da informação e do conhecimento no processo de inovação em empresas de base tecnológica - Joao Paulo Cogiola Falcao (2009)
Innovation, in its broadest definition, latu senso, has been recognized, explicitly or not, as the main reason for the modernization of the society, being in the current dominant model or in former phases of human development. In parallel, with the advent of the organizing view overknowledge brought by Information Science, information sharing has been proved of having significant role on innovation occurrence. This research is based on a comparative study, through observation and interviews, done with four technology-based enterprises and it identifies how the influence of this construct on that one occurs, under a systemic view andconsidering the social paradigm of information. It questions whether it is sustainable to privilege the traditional forms of information and knowledge sharing, based on research and development (R&D), at the expense of interaction and experience sharing and also whetherinnovation will still exist. Concludes that the technology-based enterprises do privilege the traditional forms of information and knowledge sharing, based on research and development. However, it states the interaction, with the external environment, is an endless stimuli which could become meaningful information. Matured in its culture, flavored by its history and synthesized with the ingredients of knowledge of its members, there will be the generation of new knowledge, trigger for new ideas. Innovations will emerge as solution to the day-by-day struggle and organizations survival in a movement towards the individual, which is component and builder of the organization, to where the focus must be directed. The organization does not exist without its members and only them, highlighting the plurality of its internal and external relations, will give innovation life.